Wireless electrocardiogram patch device for continuous monitoring of pediatric patient with congenital heart disease - Amir Mustakim Ab. Rashid, 1996- , author 618083; Fakulti Biosains dan Kejuruteraan Perubatan 538915 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Bio-Perubatan)) - Universiti Teknologi Malaysia, 2018